Die Zukunft der Gesetzlichen Krankenversicherung zwischen Markt und Strukturkonservatismus - Steffens, Tomas (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1997)
While public health insurance (PHI) fees keep increasing, it is not the material structural problems of the PHI system but strategies towards the privatization of sickness risks which deterrnine the discussion in health policy. This article analyzes the effects of an introduction of free-market steering mechanisms on the planning principles of a social health insurance.